Comparative Sedative Effects of Esketamine and Dexmedetomidine Versus Dexmedetomidine Alone in Patients Undergoing Spinal Tumor Surgery - Lin C; Yuan L; Shi J; Kong L; Luo N; Wang J (Therapeutics and Clinical Risk Management, 2025)
Chuanyan Lin, Liyong Yuan, Jun Shi, Lingsi Kong, Ni Luo, Jianlin Wang Department of Anesthesiology, Ningbo Sixth Hospital, Ningbo City, Zhejiang Province, 315140, People’s Republic of ChinaCorrespondence: Jianlin Wang, Department of Anesthesiology, Ningbo Sixth Hospital, 1059 Zhongshan East Road, Yinzhou District, Ningbo City, Zhejiang Province, 315140, People’s Republic of China, Tel +86 0574-87990640, Email LCY3660@163.comObjective: Esketamine and dexmedetomidine are commonly used sedatives in surgery, which can result in minimal respiratory depression and analgesic activity. This study investigated the sedative effect of esketamine combined with dexmedetomidine on patients undergoing spinal tumor (ST) surgery.Methods: We did a retrospective analysis at the Anesthesiology Department of Ningbo City’s the sixth Hospital. They studied 75 ST surgery patients who got esketamine in combination with dexmedetomidine (Group ED) between April 2022 and June 2024. In a 1:1 cohort, compare these individuals to those who only received dexmedetomidine at the same time period (Group D). The primary outcome is perioperative hemodynamic status. The secondary outcomes were pain intensity, intraoperative neurophysiological monitoring (IONM), and the occurrence of adverse responses.Results: Compared with group E, the group ED had lower mean arterial pressure (MAP), heart rate (HR), and visual-analogue scale (VAS) scores after the start of surgery (all P< 0.05). There was no significant difference in the waiting time for perioperative motor evoked potential (MEP) and the intensity of the first induced MEP current between the two groups (all P> 0.05); The Group ED first induced MEP amplitude, somatosensory evoked potential (SEP) amplitude, and MEP amplitude greater than the Group D, while SEP latency and MEP latency were smaller than the Group D (all P< 0.05). There was no significant difference in the incidence of perioperative adverse events between the two groups (P> 0.05).Conclusion: Compared with dexmedetomidine alone, the combination of esketamine and dexmedetomidine during ST surgery can demonstrated superior sedation and pain control without increasing adverse event risk, making it a viable alternative for ST surgery anesthesia.Keywords: esketamine, dexmedetomidine, spinal tumor, sedative effect